2017
DOI: 10.1371/journal.pone.0182912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salting treatment on the physicochemical properties, textural properties, and microstructures of duck eggs

Abstract: In order to illuminate the forming process of salted egg, the effects of the brine solution with different salt concentrations on the physicochemical properties, textural properties, and microstructures of duck eggs were evaluated using conventional physicochemical property determination methods. The results showed that the moisture contents of both the raw and cooked egg whites and egg yolks, the springiness of the raw egg yolks and cooked egg whites exhibited a decreasing trend with the increase in the salti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…Generally, ovomucin is a highly polymerised large molecule protein that is considered to be a key protein in the maintenance of the albumen viscosity (Omana et al , ). Ovomucin can bind to electrolytes and is very sensitive to salts (Xu et al , ). Xu et al () also reported that the viscosity of the duck egg albumen showed an overall decreasing trend after salting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, ovomucin is a highly polymerised large molecule protein that is considered to be a key protein in the maintenance of the albumen viscosity (Omana et al , ). Ovomucin can bind to electrolytes and is very sensitive to salts (Xu et al , ). Xu et al () also reported that the viscosity of the duck egg albumen showed an overall decreasing trend after salting.…”
Section: Resultsmentioning
confidence: 99%
“…Salted duck eggs are popular traditional preserved food product in China and South‐East Asian countries due to its unique flavour, texture and taste (Xu et al , ). Normally in Thailand, fresh eggs of duck were salted by coating with a paste of mud and salt (4:1 w/w), covering with rice hull ash and storing at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As oxidation progressed, the viscosity of the Ox‐OVA aqueous solution decreased with the oxidation time. This indicated that the intermolecular interaction of OVA was weakened after oxidation by hydroxyl radicals (Sheng et al, ; Xu et al, ).…”
Section: Resultsmentioning
confidence: 99%